Abiotic stress-induced regulation of antioxidant genes in different Arabidopsis ecotypes: microarray data evaluation. Issue 1 (1st January 2019) - Filiz, Ertugrul; Ozyigit, Ibrahim Ilker; Saracoglu, Ibrahim Adnan; Uras, Mehmet Emin; Sen, Ugur; Yalcin, Bahattin
Abstract: Although stresses induce generation of reactive oxygen species (ROS), which are highly reactive and toxic, and cause severe damage to cellular components; plants have very efficient enzymatic ROS-scavenging mechanisms. Despite the substantial knowledge produced about these enzymes, we still have limited knowledge regarding their expression patterns in relation to the stress type, duration and strength. Thus, taking advantage of microarray data, this work evaluated the abiotic stresses (salt, cold, heat and light) induced regulation of six antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), glutathione peroxidase (GPX), monodehydroascorbate reductase (MDHAR) and dehydroascorbate reductase (DHAR), in 10 natural Arabidopsis ecotypes. The expression profiles of 36 genes encoding six enzymatic antioxidants including CSD1-3, FSD1-3, MSD1-2, CAT1-3, APX1-6, APXT, APXS, GPX1-8, MDAR1-5 and DHAR1-4 were investigated. In particular, FSD1, FSD2, CSD1 and CSD2 genes coding for SOD; CAT2 and CAT3 for CAT; APX3-6, APXT and APXS for APX; GPX1, GPX2, GPX5, GPX6 and GPX7 for GPX; MDAR2-4 for MDHAR; and DHAR1 and DHAR3 for DHAR families appeared to be more differentially expressed under given stress conditions. Primarily, high light as well as salt and cold stresses considerably up-regulated the gene expression, whereas cold stress significantly led to the down-regulation of genes. The overall expression pattern of ecotypes suggested that the studied Arabidopsis genotypes had different stress tolerance.